Renewed Momentum in the German Housing Market: Boom or Bubble? - Xi Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2013)
The renewed momentum in the German housing market has led to concerns that Germany is vulnerable to asset price shocks. In this paper, we apply recently developed recursive unit root tests to detect the beginning and the end of potential speculative bubbles in Germany over the sample period 1987Q3 - 2012Q4. Overall, we find that actual house prices are not significantly disconnected from underlying economic fundamentals. Thus, there is no evidence of speculative house price bubbles in Germany.
Keywords: C22; C53; E52; R31; 330; Germany; house price bubbles; right-tailed unit root tests